(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Monthly environmental surveillance was carried out for three consecutive years in the coastal aquatic habitats of Mathbaria, with a view to assessing the culturability and abundance of V. cholerae. The study revealed that 93 samples (29%) out of 324 were positive for V. cholerae O1 on TCBS and TTGA culture media but no sample was found positive for V. cholerae O139 in the same culture media. On the other hand, all the water and plankton samples were found positive for V. cholerae O1 and O139 in DFA counting technique. Similarly, V. cholerae non-O1 and non- O139 were detected from all samples through culture methods throughout the investigation period. V. cholerae O139 has been found to be absolutely non-responsive to artificial enrichment and culture media with the advancement of time. Therefore, water and plankton samples can also be concluded to be the additional reservoir of V. cholerae DOI: http://dx.doi.org/10.3329/jbas.v36i1.10922 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 71-78, 2012